The Polemic of Hajj Suspension and Autonomous Manasik Guidance Amid Covid 19 Pandemic as An Alternative to Obtain Mabrur Hajj - Muh. Saidun (Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
The global co-19 pandemic changed the various settings of life, including the implementation of the Hajj and related matters such as the pattern of providing guidance to the departing pilgrims.The government is continually seeking to improve the quality of the implementation of the hajj, but it always leaves problems, one of which is the implementation of hajj manasik guidance that have not been optimal. The level of understanding of pilgrims who are relatively low on fiqh / hajj manasik has not been able to deliver them into pilgrims who have independence and endurance and become a mabrur hajj. For this reason, innovation is needed in implementation of the hajj manasik guidance that are trully effective for adequate understanding of the pilgrims to the fiqh / hajj manasik, without having to burden the budget to the governmen. An alternative that can be done is independent manasik guidance. Independent hajj manasik guidance is a manasik activities are carried out independently by prospective pilgrims, the budget is not provided by the government, and is carried out by the district religious affairs office in collaboration with a hajj officer alumni, alumni of certification hajj guidance participants, Hajj Guidance Group, Indonesian Hajj Fraternity Association, and other competent parties.